1990
DOI: 10.1080/00288233.1990.10430657
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the agronomic potential of pasture legume introductions on droughty outwash soils

Abstract: Lucerne is no more productive than traditional clovers on drought-prone, low fertility soils with acid subsoils. Introductions of a variety of alternative legumes, and in particular Lotus corniculatus (birdsfoot trefoil), were compared on a high country yellow-brown earth soil developed on outwashed plains with acid subsoils. Lines and cultivars were scored for a variety of agronomic attributes, the most important in this environment being dry matter yields, autumn production, persistence, and drought toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
4
2
Order By: Relevance
“…Therefore, all treatments produced more or less equal biomass and suppressed weeds with the same efficiency. This finding was contrary to expectations for AC, as this species was supposed to be negatively affected by drought conditions [29,52,53] and consequently its strength to suppress weeds would be lower. The unexpectedly outstanding performance of AC in the dry season, in 2016, suggests that the effect of water level in limiting the growth of AC might be alleviated by other factors (e.g., soil physical, chemical, and biological properties).…”
Section: Cover Crop Species Effectcontrasting
confidence: 84%
See 2 more Smart Citations
“…Therefore, all treatments produced more or less equal biomass and suppressed weeds with the same efficiency. This finding was contrary to expectations for AC, as this species was supposed to be negatively affected by drought conditions [29,52,53] and consequently its strength to suppress weeds would be lower. The unexpectedly outstanding performance of AC in the dry season, in 2016, suggests that the effect of water level in limiting the growth of AC might be alleviated by other factors (e.g., soil physical, chemical, and biological properties).…”
Section: Cover Crop Species Effectcontrasting
confidence: 84%
“…Therefore, all treatments produced more or less equal biomass and suppressed weeds with the same efficiency. This finding was contrary to expectations for AC, as this species was supposed to be negatively affected by drought conditions [29,52,53] and consequently its strength to suppress weeds would be…”
Section: Cover Crop Species Effectcontrasting
confidence: 82%
See 1 more Smart Citation
“…The lower germination percentage of AC than of BM under dry conditions ( Figs. 2A , 3A – 3D , 5A and 5B ) is in agreement with some studies reporting AC’s sensitivity to dry conditions ( Chapman, Dodds & Keoghan, 1990 ). However, in a recent study by Elsalahy et al (2020) , it was found that the drought resilience of AC is higher than of BM.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, it was also reported for BM that the optimal range of temperatures lies between 10 °C and 20 °C ( Sharpe & Boyd, 2019 ). Conversely, AC is a more slowly growing and comparatively drought-sensitive perennial ( Chapman, Dodds & Keoghan, 1990 ), with less tolerance to drought or high temperature ( Sheaffer et al, 2003 ), and best adapted to cool and wet areas ( Döring et al, 2013 ; Nation, 1989 ). The minimal germination temperature of AC has been given as 2 °C ( Kahnt, 2008 ) or 5 °C ( Hartmann & Lunenberg, 2013 ).…”
Section: Introductionmentioning
confidence: 99%